Compliance with legal requirement to report clinical trial results on ClinicalTrials.gov: a cohort study. Issue 10221 (1st February 2020) - DeVito, Nicholas J; Bacon, Seb; Goldacre, Ben
Summary: Background: Failure to report the results of a clinical trial can distort the evidence base for clinical practice, breaches researchers' ethical obligations to participants, and represents an important source of research waste. The Food and Drug Administration Amendments Act (FDAAA) of 2007 now requires sponsors of applicable trials to report their results directly onto ClinicalTrials.gov within 1 year of completion. The first trials covered by the Final Rule of this act became due to report results in January, 2018. In this cohort study, we set out to assess compliance. Methods: We downloaded data for all registered trials on ClinicalTrials.gov each month from March, 2018, to September, 2019. All cross-sectional analyses in this manuscript were performed on data extracted from ClinicalTrials.gov on Sept 16, 2019; monthly trends analysis used archived data closest to the 15th day of each month from March, 2018, to September, 2019. Our study cohort included all applicable trials due to report results under FDAAA. We excluded all non-applicable trials, those not yet due to report, and those given a certificate allowing for delayed reporting. A trial was considered reported if results had been submitted and were either publicly available, or undergoing quality control review at ClinicalTrials.gov . A trial was considered compliant if these results were submitted within 1 year of the primary completion date, as required by the legislation. We described compliance with the FDAAA 2007 Final Rule, assessed trial characteristics associated with results reporting using logistic regression models, described sponsor-level reporting, examined trends in reporting, and described time-to-report using the Kaplan-Meier method. Findings: 4209 trials were due to report results; 1722 (40·9%; 95% CI 39·4–42·2) did so within the 1-year deadline. 2686 (63·8%; 62·4–65·3) trials had results submitted at any time. Compliance has not improved since July, 2018. Industry sponsors were significantly more likely to be compliant than non-industry, non-US Government sponsors (odds ratio [OR] 3·08 [95% CI 2·52–3·77]), and sponsors running large numbers of trials were significantly more likely to be compliant than smaller sponsors (OR 11·84 [9·36–14·99]). The median delay from primary completion date to submission date was 424 days (95% CI 412–435), 59 days higher than the legal reporting requirement of 1 year. Interpretation: Compliance with the FDAAA 2007 is poor, and not improving. To our knowledge, this is the first study to fully assess compliance with the Final Rule of the FDAAA 2007. Poor compliance is likely to reflect lack of enforcement by regulators. Effective enforcement and action from sponsors is needed; until then, open public audit of compliance for each individual sponsor may help. We will maintain updated compliance data for each individual sponsor and trial at fdaaa.trialstracker.net . Funding: Laura and John Arnold Foundation.